Pericytoma With t(7;12): The First Ovarian Case Reported and a Review of the Literature. (September 2019) - Koh, Nicholas Wee Chong; Seow, Wan Yi; Lee, York Tien; Lam, Joyce Ching Mei; Lian, Derrick Wen Quan
Abstract : We report the first case of an ovarian pericytoma with t(7;12). An 11-year-old child presented with abdominal pain and distension. A suprapubic mass was detected on examination and radiological investigations revealed a 16.5 cm solid-cystic ovarian mass. Histologically, the tumor was composed of spindle cells with S100-protein, Bcl-2, and CD10 reactivity on immunohistochemistry. Alpha fetoprotein, calretinin, alpha-inhibin, WT1, smooth muscle actin, caldesmon, desmin, cytokeratins, chromogranin, synaptophysin, EMA, Sox10, CD117, CD31, CD34, and CD68 were all negative. Molecular tests showed t(7;12)(p22;q13), resulting in the fusion of the ACTB with GLI1 genes and a diagnosis of pericytoma with t(7;12) of the ovary was made. We discuss the difficulties in diagnosing this lesion in the ovary and highlight the importance on molecular tests in characterizing challenging cases, especially primary ovarian spindle cell mesenchymal tumors.